Reasoning strategies and prior knowledge effects in contingency learning. - Béghin, Gaëtan; Markovits, Henry (Memory & Cognition, 2022)
Prior knowledge has been shown to be an important factor in causal judgments. However, inconsistent patterns have been reported regarding the interaction between prior knowledge and the processing of contingency information. In three studies, we examined the effect of the plausibility of the putative cause on causal judgments, when prior expectations about the rate at which the cause is accompanied by the effect in question are explicitly controlled for. Results clearly show that plausibility has a clear effect that is independent of contingency information and type of task (passive or active). We also examined the role of strategy use as an individual difference in causal judgments. Specifically, the dual-strategy model suggests that people can either use a Statistical or a Counterexample strategy to process information. Across all three studies, results showed that Strategy use has a clear effect on causal judgments that is independent of both plausibility and contingency.